Numerical investigation of time dependent behavior of geosynthetic reinforced piled embankments. Issue 3 (July 2013) - Bhasi, Anjana; Rajagopal, K
Abstract : In the recent years, the geosynthetics have been used in combination with columnar systems to support embankments over soft soils. The application of the geosynthetics in the embankment fill above the columns enhances the load transfer from the soil to columns, reduces the total and differential settlements and also found to be economical. This paper presents the influence of various parameters like the embankment fill properties, the stiffness of geosynthetic, and the modulus of pile on the time dependent behavior of piled embankments. The numerical models in this study were calibrated against the reported field data of a highway embankment. The numerical predictions are analyzed in terms of arching height, settlements, axial loads, geosynthetic tension, and excess pore pressures.